Pengembangan Praktikum Kimia Organik 1 menggunakan Aplikasi Adobe Flash - Dewi Handayani; Agus Sundaryono (PendIPA Journal of Science Education, 2020)
The purposes of this research are to develop the practicum of organic chemistry 1 by using the Adobe Flash application and to describe the students feasibility and response to the practicum developed. This type of research used in this research is research and development. The sample in this research is 3rd semester students of Chemistry Education Study Program in the academic year of 2018/ 2019. The instruments used in this research are validation sheets of material and media experts and response questionnaires students after testing. Based on the results of research that has been done, several stages of development ranging from problem identification, data collection, product design, design validation, design revision, and product trials have been carried out. The results of the validation of material experts obtained an average of 4,20 (very valid category) and an average media expert of 4.275 (very valid category). For the readability test of the developed guide, it was obtained 4.204 (very interesting category and student response was 3,936 (interesting category). Based on the results of expert validation and testing to students, the development of the organic chemistry 1 practicum guide was feasible to be applied in learning activities in class.